In Vivo Biological Evaluation of Ethyl 4-(7-hydroxy-4-methyl-2-oxoquinolin-1-ylamino)-coumarin-3-carboxylate as an Antitumor Agent - Mohammed, Faten Z.; Rizzk, Youstina W.; Abdelhamid, Moustafa S.; El-Deen, Ibrahim M. (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Hybridization of coumarin moiety with additional antitumor pharmacophores is an auspicious stratagem to afford precious therapeutic interference for the medication of cancer. Objective: The present study aimed to evaluate the antitumor activity of ethyl 4-(7-hydroxy-4-methyl-2- oxoquinolin-1-ylamino)-coumarin-3-carboxylate against Ehrlich Ascites Carcinoma (EAC) cells in the peritoneal cavity of female mice. Methodology: Molecular docking was used to predict the binding between the test compound and the receptor of breast cancer mutant 3HB5-oxidoreductase, as well as the viability of tumor cells and life span prolongation. The total anti-oxidant capacity was evaluated in the liver and kidneys. Serum alanine transaminase, aspartate transaminase, albumin, total protein, creatinine, and urea were estimated. The concentrations of Bcl-2 and Bax were measured in the liver and kidney tissues. Histopathological examination of the liver and kidney tissues was also carried out. Results: EAC-bearing mice injected with the test compound showed a highly significant decrease in tumor cell viability by 100%, compared to the EAC control. Also, it exhibited significant anti-oxidant and apoptotic agents through the results of total anti-oxidant capacity and apoptosis assays. Confirmed by histological examination, the results of the liver and kidney function tests revealed that the test compound had no harmful effect on either of the organs. The docking investigation disclosed an auspicious interaction between the test compound and the receptor (3HB5). To confirm these results, correlations between different parameters were carried out. It was found that there were significant positive and negative correlations between the parameters. Conclusion: Hybrid molecules containing coumarin and quinolinone exhibited a potential antitumor effect against EAC cells by the induction of apoptosis and anti-oxidant activities. Results of liver and kidney function tests and the histopathological study revealed that the administration of the test compound nullified most of the pathological alterations induced by EAC cells in mice. Based on these findings, the test compound can be developed as an effective chemotherapeutic agent.
Keywords: ehrlich ascites carcinoma